Reward Manajemen untuk Membentuk Psychology Well-being dalam Mengurangi Terjadinya Demo - Muhammad Alif Yudha; Soffy Balgies; Yunia Lailatul Mafuz; Triningtyas Triningtyas (Bina Nusantara University, 2021)
The purpose of this journal research is to find how to provide salary system and THR to employees at PT Crevis Tex Jaya Subang West Java and analyze the impact and solution. With the method of reviewing case studies at PT Crevis Tex Jaya Subang West Java caused by the late payment of salaries to employees of PT Crevis Tex Jaya even THR still delinquent and make the employees down action or demo to demand their rights. Salary giving and THR have applicable invitations.